Desengajamento moral e assédio sexual com mulheres nas mídias sociais - PEREIRA, Karla Fernanda (2019)
This study search to answer which are the mechanisms of moral disengagement most present in cases of sexual harassment with women in social media. Based on the observation that sexual harassment with women is something so common in Brazil, especially in social media, and little studied, despite the psychological damages caused to the victims, and that those who practice sexual harassment are morally disengaged, it was researched concerning moral disengagement, harassment and questions about the digital society, and cases of sexual harassment in social media were analyzed to observe the mechanisms of moral disengagement most used in this practice. The methodology is bibliographical research of an interdisciplinary approach, in that besides Social Psychology, issues related to Sociology and Anthropology are addressed; and discourse analysis. Information was searched in newspapers and magazines online, with reports of sexual harassment with women in social media, in which the aggressor is Brazilian. From the analysis of content it was possible to analyze the speech of the harasser and the content present in the aggressions to the victims, through postings, and testimonies and narratives of the harassed brought by newspapers and online magazines. Discourse analysis allowed the study of the anthropological and social influences in Brazilian culture regarding sexual harassment in social media. It was observed that the mechanisms of moral disengagement most common in cases of sexual harassment analyzed were attribution of guilt, dehumanization, euphemistic language, contempt of consequences and diffusion of responsibility. The relevance of the research is due to its timeliness, since it deals with current and recurrent problems, and it is hoped that the results found contribute to a better understanding of sexual harassment and to promote reflection on moral disengagement in relation to women.